Verbal fluency predicts mortality in Alzheimer’s disease - Cosentino, S. (2006)
OBJECTIVES: To assess the predictive value of neuropsychological profiles, at diagnosis, for mortality in incident Alzheimer’s disease (AD). BACKGROUND: Rate of AD progression varies significantly across individuals for reasons that are not well understood. Several studies have linked rapid decline with disproportionately impaired executive functioning, presumably reflecting greater impairment of frontal networks. To the extent that differential neuropsychological profiles reflect various neuropathologic presentations of AD, such profiles may inform survival estimates early in the disease. METHODS: Five neuropsychological indices were used to characterize performance in 161 individuals at diagnosis during of Alzheimer’s disease during a 15-year, longitudinal, primarily community-based study. RESULTS: 52% of participants reached the mortality endpoint with a median survival of 5.52 years (95% CI, 4.41 – 6.63). Cox proportional hazards analyses indicated that older age at diagnosis was associated with higher risk of mortality (RR, 1.08; 95% CI, 1.04 –1.12) while Hispanic ethnicity predicted lower mortality (0.22 [.09 – .55]). Controlling for these two demographic variables, higher verbal fluency scores at diagnosis predicted lower mortality (0.69 [0.49 – 0.96]). CONCLUSIONS: Disproportionate impairment of both category and letter fluency at the earliest stages of AD predicts mortality. The prognostic value of these tests may derive from their general psychometric properties, or may reflect the measures’ sensitivity to an early or critical level of compromise to frontal networks.